A phosphodiesterase 3B-based signaling complex integrates exchange protein activated by cAMP 1 and phosphatidylinositol 3-kinase signals in human arterial endothelial cells. - Wilson, L; Baillie, G; Pritchard, L; Umana, B; Terrin, A; Zaccolo, M; Houslay, MD; Maurice, D (2011)
Enzymes of the phosphodiesterase 3 (PDE3) and PDE4 families each regulate the activities of both protein kinases A (PKAs) and exchange proteins activated by cAMP (EPACs) in cells of the cardiovascular system. At present, the mechanisms that allow selected PDEs to individually regulate the activities of these two effectors are ill understood. The objective of this study was to determine how a specific PDE3 variant, namely PDE3B, interacts with and regulates EPAC1-based signaling in human arterial endothelial cells (HAECs). Using several biochemical approaches, we show that PDE3B and EPAC1 bind directly through protein-protein interactions. By knocking down PDE3B expression or by antagonizing EPAC1 binding with PDE3B, we show that PDE3B regulates cAMP binding by its tethered EPAC1. Interestingly, we also show that PDE3B binds directly to p84, a PI3Kγ regulatory subunit, and that this interaction allows PI3Kγ recruitment to the PDE3B-EPAC1 complex. Of potential cardiovascular importance, we demonstrate that PDE3B-tethered EPAC1 regulates HAEC PI3Kγ activity and that this allows dynamic cAMP-dependent regulation of HAEC adhesion, spreading, and tubule formation. We identify and molecularly characterize a PDE3B-based "signalosome" that integrates cAMP- and PI3Kγ-encoded signals and show how this signal integration regulates HAEC functions of importance in angiogenesis.